2020
DOI: 10.3390/jmse8060382
|View full text |Cite
|
Sign up to set email alerts
|

Commercial Performance of Blue Mussel (Mytilus edulis, L.) Stocks at a Microgeographic Scale

Abstract: Bivalve aquaculture is an important component of the economy in eastern Canada. Because of current social, environmental, economic, and resource constraints, offshore mussel cultivation seems to be a promising strategy. With the objective of optimizing farming strategies that support the sustainability and development of the mussel industry at a microgeographic scale, we evaluated, after a traditional two year production cycle, the commercial performance of spat from several mussel (Mytilus edulis) stocks orig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Some authors were interested in comparing the farming production (Camacho et al 1995;Okumus & Stirling 1998;Fuentes et al 2009), taking into account response variables such as growth (Fernandez-Reiriz et al 1996;Hatzonikolakis et al 2017) and condition index (Okumus & Stirling 1998). Guillou et al (2020) studied the commercial performance of the blue mussel in Canada. Theodorou et al (2014) reported that the optimal farm size for mussel production of the Mediterranean mussel in Greece is a larger than 3 ha.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors were interested in comparing the farming production (Camacho et al 1995;Okumus & Stirling 1998;Fuentes et al 2009), taking into account response variables such as growth (Fernandez-Reiriz et al 1996;Hatzonikolakis et al 2017) and condition index (Okumus & Stirling 1998). Guillou et al (2020) studied the commercial performance of the blue mussel in Canada. Theodorou et al (2014) reported that the optimal farm size for mussel production of the Mediterranean mussel in Greece is a larger than 3 ha.…”
Section: Introductionmentioning
confidence: 99%